Vertical migration of Haemonchus contortus third stage larvae on Brachiaria decumbens grass - Silva, B. F. [UNESP]; Amarante, M. R. V. [UNESP]; Kadri, S. M. [UNESP]; Carrijo-Mauad, J. R. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2008)
The present study aimed at evaluating the vertical migration of Haemonchus contortus third stage larvae (1-3) on Brachiaria decumbens grass, as well as at verifying whether larval numbers on pasture varies over the day due to climatic conditions. Feces containing H. contortus L3 were deposited on the soil in the middle of herbage which was initially 30 cm high. Seven days later, samples of different herbage strata (0-10, 10-20 and >20 cm), remaining feces and a layer of approximately 1 cm soil were collected. Tests were carried out in four periods: September 2006, December 2006, March 2007, and June 2007. Samples were collected at sunrise, mid-day, sunset, and mid-night. The humidity and temperature conditions observed in different months influenced larval migration from the feces to the grass. In September, December and March, it rained after fecal deposition on pasture, which favored migration of larvae from the feces to the herbage. Conversely, in June 2007, when there was no rainfall after fecal deposition and temperatures were lower, L3 were mainly recovered from feces. As regards the vertical migration of larvae, the numbers of H. contortus L3 in the forage strata remained relatively constant over the day. This indicates there is not a determined period in which sheep on pasture are at higher risk of infection. Finally, in all collection periods a considerable amount of third stage larvae was observed on the herbage top, which is the first plant part consumed by sheep. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Vertical migration; Third stage larvae; Haemonchus contortus; Pasture; Sheep; Brachiaria decumbens